2015
DOI: 10.1111/1365-2435.12600
|View full text |Cite
|
Sign up to set email alerts
|

From steps to home range formation: species‐specific movement upscaling among sympatric ungulates

Abstract: Summary Animals move to interact with the environment in order to find food resources and cover. Intrinsic characteristics affecting feeding and antipredatory strategies likely shape variation in movement patterns and home range formation between individuals, populations and species. Browsing herbivores selectively forage on patchily distributed resources in areas with more canopy cover, whereas mixed feeders and grazers feed on more open grasslands and tend to aggregate as an antipredatory strategy. We ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 98 publications
(181 reference statements)
0
8
0
Order By: Relevance
“…In contrast, higher proportions of forest may provide increased shelter and protection for resident roe deer (Tablado et al. ), emphasizing the importance of the ratio of costs and benefits of migration. Interestingly, Tablado et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In contrast, higher proportions of forest may provide increased shelter and protection for resident roe deer (Tablado et al. ), emphasizing the importance of the ratio of costs and benefits of migration. Interestingly, Tablado et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Tablado et al. () found that roe deer concentrate their movement in fairly small areas selecting higher quality food and are able to forage optimally due to their solitary social system. Thus, if fine‐scale forage diversity is sufficiently high in resident ranges, residency may be the more beneficial tactic for this small browser.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This species is so a particularly relevant model to seek for a functional response vis-à-vis a continuously distributed resource variable, which can be characterized by both a mean value and a spatial variation. We leveraged a unique combination of three large data sets on habitat characteristics (distribution, composition, and biomass of plant communities) defined through remote sensing and field sampling (Duparc et al 2012;Duparc 2016), individual habitat use obtained by GPS collars (Tablado et al 2016), and diet, determined using DNA barcoding (Bison 2015;Thuiller et al 2017). More specifically, we determined the shape of the functional response by comparing habitat selection patterns among individuals from several subpopulation units monitored throughout the growing season.…”
Section: Original Articlementioning
confidence: 99%